The Trajectory of the Albanian Historiography: Between the Austrian Albanologie (Volkskunde) and the Communist Albanologie (National-Stalinism/Etnographiya) - Bezha, Anastas (Études sur la Région Méditerranéenne, 2021)
The focus of this paper is to analyze the trajectory of the Albanian historiography before and during communism. After the fall of the communist regime in 1991, the related studies on this subject were focused on the main narratives proposed by this historiography, with a critical eye by the German-speaking community of researchers. In this regard, little effort has been put to analyze the context – scientific and political – how these two closely resembling narratives were created. The paper tries to show a clear evolutionary path of the Albanian Historiography initiated by the actions of the Ballhausplatz in the last decade of the century XIX, as part of the literary propaganda towards the Albanians, up to the adoptions and distortions of the same teachings by the communist historians half a century later. Such evolution passed through two major steps: the transition from the scientific tradition of Volkskunde als Volksgeschichte to its sibling version of Soviet Etnographiya; and further on to the implementation of the historiographic archetype work of the Hungarian historian Lajos Thallóczy in the new textbooks by the Albanian communist historians.